La dernière étape de la carrière politique de Floridablanca - Gérard Dufour (Mélanges de la Casa de Velázquez, 2009)
The funeral eulogies that followed the decease of Floridablanca stressed the recognition that Spain owed him, particularly for his activity as president of the Junta Central. Indeed, from the time of the creation of the Junta Suprema of Murcia to that of the Junta Central, the Count spared no effort to rein in the anarchy, which he believed could fuel popular movements hostile to the French presence. His experience equipped him to overcome the resistance of those who claimed that the Junta Central would usurp the legitimate authority of the sovereign, and under his presidency this new body pursued an extremely conservative policy, characterised particularly by measures favourable to the interests of the Church. The panic that he experienced on hearing of Napoleon's advance on Madrid and his ensuing flight did not prevent his triumphal reception in Seville, the city where he would eventually die.